Erosion at the inner wall of JET during the discharge campaign 2013–2014. (May 2017) - Krat, S.; Mayer, M.; Bykov, I.; Lungu, C.P.; Aubin, G. de Saint; Widdowson, A.; Carvalho, I.S.
Highlights: Erosion in the recessed areas of the inner wall during the second JET-ILW campaign was studied. Rate and distribution of W erosion were the same as in first JET-ILW campaign and JET-C campaigns. Erosion of Be decreased by a factor of about 2. Abstract: The erosion of Be and W marker layers was investigated using long-term samples containing marker layers during the second ITER-like wall discharge campaign 2013–2014 (ILW-2). The samples were mounted in Be coated Inconel tiles between the inner wall guard limiters (IWGL). They were analyzed using elastic backscattering (EBS) before and after exposure. All samples showed noticeable erosion. The results were compared to the data for Be and W erosion rates for the first 2011–2012 JET ITER-like wall (ILW-1) campaign, and to the data for C erosion during the 2005–2009 campaign when JET was operated with a carbon wall. The mean W erosion rates and the toroidal and poloidal distributions of the W erosion were nearly the same for the ILW-1 and ILW-2 campaigns. The mean erosion rate of Be during the ILW-2 campaign was smaller by a factor of about two compared to the ILW-1 campaign.